Integrating Eco-Theology In Islamic Education: A Case Study On Fostering Ecological Awareness Through Religious Pedagogy - Taufikin, Taufikin (el-Tarbawi, 2025)
This study investigates the operationalization of eco-theology in Islamic education and its effects on students’ environmental awareness and behavior. Anchored in the Qur’anic principles of khilāfah (vicegerency), amānah (trusteeship), and mizān (balance), the research employs a qualitative case-study design across three Islamic elementary schools in Demak that have instituted eco-theology–based programs. Data were collected through semi-structured interviews, classroom and schoolyard observations, and document analysis. The analytic procedure involved iterative reduction, categorical coding, and interpretive synthesis, followed by source triangulation to enhance credibility. The findings show that integrating eco-theology into the curriculum substantially strengthens students’ understanding of the connection between Islamic teachings and ecological responsibility while fostering tangible pro-environmental practices, including reforestation activities, structured waste management, and prudent energy use. Experiential learning and consistent teacher modeling emerged as decisive drivers of students’ ecological conduct. Nonetheless, implementation is constrained by limited instructional materials, uneven teacher training, and the absence of systematic, school-wide eco-theological policies. Policy implications indicate the need for comprehensive eco-theology curricula, sustained professional development for teachers, and governance frameworks that institutionalize environmental stewardship. Schools should formalize supportive policies and cultivate partnerships among educational institutions, academics, and environmental organizations to build a more sustainable and integrated learning ecosystem.